2020
DOI: 10.1177/0894486520917774
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Antecedents of Decision Comprehensiveness and Their Relationship to Decision Quality and Performance in Family Firms: An Upper Echelons Perspective

Abstract: We present a model of family firm performance that tests the notion that strategic decision comprehensiveness plays a pivotal role in family business decision quality and performance. With insights derived from upper echelons theory, our model further proposes that two key decision maker traits associated with an individual’s information-gathering process—risk-taking propensity and need for cognition—influence strategic decision comprehensiveness and have indirect effects on both study outcomes. Study results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 60 publications
1
35
0
Order By: Relevance
“…Students might then consider the psychological foundations of management in family firms (values, heuristics, and biases, but also emotions, experiences, and memories) as a springboard for understanding family firm decisions. For example, future family firm leaders should be aware that their own risk-taking propensity and thoughtfulness will affect the quality of the strategic decision processes, and in turn, firm performance (Carr et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students might then consider the psychological foundations of management in family firms (values, heuristics, and biases, but also emotions, experiences, and memories) as a springboard for understanding family firm decisions. For example, future family firm leaders should be aware that their own risk-taking propensity and thoughtfulness will affect the quality of the strategic decision processes, and in turn, firm performance (Carr et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…We next summarize the four articles in this issue. Assuming a reductionist approach to the psychological foundations of management, Carr et al (2020) enrich the literature on the psychological antecedents of decision comprehensiveness by focusing mainly on the heuristics and biases square in our proposed framework. The authors argue that the propensity to take risks and the desire to have time to think acutely about problems are two bases on which executives start making strategic decisions.…”
Section: The Articles In This Special Issuementioning
confidence: 99%
“…Heeding this call, Picone, De Massis, Tang and Piccolo (2021) built a conceptual framework linking the psychological foundations of management in family business, strategic decision-making, and firm performance. The first issue of the Family Business Review special issue discusses some of Picone et al’s (2021) key constructs: decision comprehensiveness (Carr, Vardaman, Marler, McLarty, & Blettner, 2020), values (Ruf, Graffius, Wolff, Moog, & Felden, 2020), overconfidence (Dick, Wagner, & Pernsteiner, 2020), and Machiavellism (Chandler, Petrenko, Hill, & Hayes, 2020).…”
mentioning
confidence: 99%
“…Then managers can improve their strategic understanding of the environment by being more comprehensive. Studies have shown that the comprehensiveness of strategic decision-making for family firms is positively associated with decision-making quality and firm performance ( Carr et al, 2020 ). Miller (2008) study showed that, in a turbulent environment, both linear and non-linear relationships between comprehensiveness and performance are significantly positive.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%